Pityriasis Rosea in a Pregnancy - Karaer, Abdullah; Beyhan, Seyhan; Şahin, Fikret (Gynecology Obstetrics & Reproductive Medicine, 2012)
A pregnant woman with Pitriasis rosea whose lesion onset is in first trimester is presented. No interventions were undertaken and her eruption remitted completely 6-7 weeks. We found no evidence of active infection for HHV-6 and HHV-7. A girl with a birth weight 2000 kg was born at 34 weeks and 6 days. She had to stay in the neonatal intensive care unit for 5 days. The baby is now 6 months of age and is healthy. In order to evaluate whether PR especially when it develops within the first weeks’ gestation, is associated with adverse pregnancy outcome, further investigations are required.